Stakeholder engagement the game changer for program management - Baugh, Amy (Best practices and advances in program management series, 2015)
Strong stakeholder engagement is perhaps the most critical factor for achieving successful program execution in our fast-paced world. Many program managers get stuck in the "science" of program management, spending vast amounts of effort on tasks, charts, and metrics. Program managers who emphasize activities around relationship building and stakeholder engagement usually have the best chance for program success. This book focuses on how to engage your stakeholders in the right way, and keep them engaged throughout the course of your program.